Internal Control Analysis and Fraud Prevention Efforts in Public Sector Accounting - Kurniawan, Awi; Haliah, Haliah; Kusumawati, Andi (PT FORMOSA CENDEKIA GLOBAL, 2024)
The study examines the role of internal control in preventing fraud within public sector accounting by safeguarding assets, ensuring accurate financial reporting, and promoting operational efficiency. Internal control systems are built on control environments, risk assessments, control activities, communication, and monitoring. Weak internal controls, such as inadequate segregation of duties and poor oversight, often lead to fraud in the public sector. Effective measures, including audits, anti-fraud policies, ethical behavior promotion, and the use of technology for monitoring, can mitigate these risks. Strengthening internal control systems enhances financial integrity, protects public resources, and supports efficient governance.